PENGARUH IMPLEMENTASI PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE TERHADAP KINERJA MANAJERIAL PADA BANK PEMBANGUNAN DAERAH (BPD) DAERAH ISTIMEWA YOGYAKARTA - Nur Hidayah; Alia Ariesanti (Universitas Ahmad Dahlan, 2013)
Implementation of good corporate governance in banks is expected to eliminate mismanagement, forming a system of checks and balances that guarantee effective and all-powerful corporation in line with improving corporate performance through the creation process of making better decisions, improve operational efficiency and further improve services to stakeholders. The study was conducted to provide empirical evidence of the influence of the implementation of good corporate governance on managerial performance in Yogyakarta BPD Bank. Research object is the middle and lower level managers in the Regional Development Bank (BPD) Special Region of Yogyakarta. The data used are the primary data from respondents' answers, theÂ manager at the Bank BPD DIY. This study uses multiple linear regression analysis. The results showed that: (1) Transparency affect managerial performance. (2) Accountability affect managerial performance. (3) Responsibility affect managerial performance. (4) independency affect managerial performance. (5) Fairness does not affect managerial performance